Comment on Tzeng et al: Caffeinated chewing gum improves sympathetic nerve activity and wrestling performance - Petrosyan, T. (International Journal of Sports Physiology and Performance, 2026)
I read with interest the article by Tzeng et al1 examining the effects of caffeinated chewing gum on sympathetic nerve activity and simulated wrestling performance. While the study addresses a practically relevant topic and employs a double-blind crossover design, several methodological and conceptual limitations warrant consideration.